From The History Of World Psychiatry: Chronological Table - Vovk, Olga (Psychiatry, Neurology and Medical Psychology)
In the present paper the history of psychiatry is presented in the form of a chronological table. The process of developing knowledge about the essence of mental illnesses and methods for their treatment, organization of mental health care, and the formation of psychiatry as scientific and educational discipline were represented as six legitimate steps. They correlated with main stages of European civilization development: pre-scientific era; ancient era (VIII century BC – V century CE); medieval era (V–XVI centuries); Enlightenment (XVII – beginning of XIX centuries); industrial era (beginning of XIX century – first half of XX century); current time (second half of XX century – first half of XXI century). At the same time these steps mark tectonic shifts that took place in history of psychiatry. A brief description of every stage was given. Evidences that make it possible to trace the evolution of ideas about the nature of mental illness were described. Also public attitude to mental patients in different historical periods was explored. Special attention has been given to the contribution of Ukraine and Kharkiv in psychiatry development.